2021
DOI: 10.1002/aic.17465
|View full text |Cite
|
Sign up to set email alerts
|

Selective aqueous ammonia sensors using electrochemical stripping and capacitive detection

Abstract: Managing waterborne ammonia-nitrogen pollution requires monitoring distributed wastewater nitrogen discharges. In this study, we demonstrated and investigated a proof-ofconcept sensor that combines selective electrochemical separation and sensitive capacitive detection for sensing total ammonia nitrogen (TAN). By varying TAN concentration in synthetic ammonia-polluted water (up to 50 mg/L), we selectively separated ammonia nitrogen from feedwater into a sulfuric acid solution, in which capacitance decreased li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Our previous nitrogen recovery studies using ECS indicated that the recovery efficiency varied with the influent nitrogen concentration. 24,36 We expected EXS to be more compatible with fluctuating nitrogen concentrations because it separates nitrogen from urine onto resins; indeed, three nearly identical ammonium breakthrough curves were again observed with concentrated synthetic urine, albeit with half as many bed volumes (Figure S18a). The mass of ammonium removed by the resin was identical for synthetic and real urine (around 300 mg NH 4 + for the 12 mL resin used, Figure S18b), which demonstrated that resin equalized nitrogen loading from different streams.…”
Section: Rate-limitingmentioning
confidence: 92%
See 1 more Smart Citation
“…Our previous nitrogen recovery studies using ECS indicated that the recovery efficiency varied with the influent nitrogen concentration. 24,36 We expected EXS to be more compatible with fluctuating nitrogen concentrations because it separates nitrogen from urine onto resins; indeed, three nearly identical ammonium breakthrough curves were again observed with concentrated synthetic urine, albeit with half as many bed volumes (Figure S18a). The mass of ammonium removed by the resin was identical for synthetic and real urine (around 300 mg NH 4 + for the 12 mL resin used, Figure S18b), which demonstrated that resin equalized nitrogen loading from different streams.…”
Section: Rate-limitingmentioning
confidence: 92%
“…WD-based EIX can avoid close resin–electrode contact, especially when protons are produced by WD in bipolar membranes (BPMs). Only ex situ BPM-assisted regeneration has been demonstrated, making BPM-assisted in situ regeneration a promising but underexplored approach for enhancing process intensification. …”
Section: Introductionmentioning
confidence: 99%
“…83 Mild basic solution can be readily produced with electrochemical approaches, such as water splitting. 46,65,88,89 With a simple electrochemical reactor containing two electrodes and an ion exchange membrane (Fig. 7a), the electrolyte pH can readily be elevated to pH 11 even with a low current density.…”
Section: Ligand-selective Hybrid Anion Exchanger: Donnan-principle Fo...mentioning
confidence: 99%
“…Besides, Schlumpberger et al developed 108 a electrochemical water treatment method called “Shock electrodialysis,” which shows promise for water deionization and ionic separations. Lalwani et al investigated 109 a proof of concept sensor dependent on electrodialysis technology for sensing total ammonia nitrogen (TAN).…”
Section: Electro‐membrane Reactormentioning
confidence: 99%